2017
DOI: 10.5430/jnep.v7n8p7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting medication adherence among patients with rheumatic disorders

Abstract: Background and objective: Patient's adherence is an important factor affecting the successful maintenance of treatment, slow progression of the disease; reduce costs of health care especially in the presence of multiple chronic conditions as rheumatic disorders. While, medication non-adherence is a significant problem leads to increased mortality and morbidity. So, identification of the factors affecting non-adherence to medication regimens is beneficial for healthcare providers to improve patient's health con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…However, non‐adherence to medication is a threat to improving healthcare outcomes leading to unnecessary hospitalization and mortality . The term medication adherence in this context indicates a patient takes medication regularly as directed by a prescriber …”
Section: Introductionmentioning
confidence: 99%
“…However, non‐adherence to medication is a threat to improving healthcare outcomes leading to unnecessary hospitalization and mortality . The term medication adherence in this context indicates a patient takes medication regularly as directed by a prescriber …”
Section: Introductionmentioning
confidence: 99%
“…Findings from the literature review revealed that approximately 50% of patients do not take medications as prescribed, which is associated with poorer outcomes, relapse, increased mortality, and hospital admissions (O'Malley, 2013). The reason behind this non adherence is the lack of continuity of care, patient information materials written at too high literacy level, lack of knowledge on adherence, and the medication cost are few of the many reasons that contribute to non adherence (Ismail, Selim, & Elkhashab, 2017).…”
Section: Significance and Justificationmentioning
confidence: 99%
“…With the exception of classical works, the search is limited to the years 2013 to 2018 to ensure that current evidencebased literature was reviewed and summarized for the purpose of this project. A summary of the review of the literature is presented.Reason for Non Compliance to MedicationsAccording toIsmail, Selim, & Elkhashab (2017), lack of continuity of care, patient information materials written at too high literacy level, lack of knowledge on adherence, and the medication cost are few of the many reasons that contribute to non adherence Khan, Shah, & Hameed (2014). considers side-effects and forgetfulness as the main barriers to low medication adherence.…”
mentioning
confidence: 99%
“…The content of this part was developed by the researcher after passing through an extensive and relevant literature review to assess patient's compliance with nursing instructions as (dietary instructions and early detection and avoidance of precipitating factors). It included (20) questions with a yes or no response. Every question was given one score, a score of zero was given for a negative response while a score of one was given for a positive response (Yes= 1; No= 0).The total scores was (20) score.…”
Section: Tool Ii: Compliance Assessment Questionnaire It Included Twomentioning
confidence: 99%